An M−shaped buckled beam for enhancing nonlinear energy harvesting. (1st April 2023) - Chen, Kunming; Ding, Xiaoliang; Tian, Libin; Shen, Hui; Song, Rujun; Bian, Yixiang; Yang, Qian
Graphical abstract: Highlights: M−shaped beam has a monostable or bistable state determined by the clamping distance. Monostable configuration has nonlinear softening or hardening behavior. Potential well depth can be adjusted by the clamping angle. Shallower potential well causes better output power and operation bandwidth. Exploiting bistable configuration brings 105% bandwidth and 349% RMS power increase. Abstract: Aiming to achieve the high-performance piezoelectric energy harvester under low excitation, a bistable energy harvester with an M−shaped buckled beam is proposed in this paper. When the M−shaped beam is pre-compressed into a buckling state, motion of the M−shaped beam has changed from monostable oscillation to bistable oscillation. Compared with the original monostable M−shaped beam, numerical and experimental results show that the proposed harvester can easily maintain large-amplitude interwell oscillation and offer a wider operation bandwidth in lower frequency range. The harvester can offer an operation bandwidth of 5 Hz or 6 Hz under 3 m/s 2 or 5 m/s 2 excitation, which is improved by 233.3 % or 140 % in comparison with the monostable configurations. In bistable configurations, the acceleration threshold required for interwell oscillation can be decreased by reducing the buckling level, which can provide higher voltage and wider operation bandwidth in sweep frequency excitation. In monostable configurations, it is observed that the M−shaped beam shows a softening behavior or a hardening behavior with different clamping distance. Numerical and experimental results verify that the performance of monostable configuration with a softening behavior is better than that with a hardening behavior.